2009
DOI: 10.1002/syn.20617
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in dopamine‐stimulated gene expression after single‐day methamphetamine exposure

Abstract: Methamphetamine (mAMPH) is a highly addictive psychostimulant drug that injures monoaminergic neurons and results in behavioral impairments in humans and animals. Although evidence exists for changes in cortical volume, metabolism, and blood oxygenation levels in human mAMPH abusers, animal models have instead emphasized this drug's long-lasting influence on ascending monoaminergic (dopamine, serotonin) projections. The aim of this study was to investigate cortical and subcortical function in rats long after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…A single-day of binge mAMPH has been reported to result in cortical changes, affecting metabolism and gene expression in several cortical areas (Pontieri et al 1990; Belcher et al 2009). Such functional 5-HT changes can occur secondarily to changes in DA transmission (Marshall et al 2007; Belcher et al 2009) and might predispose the organism to work and/or delay aversion. Serotonin in the frontal cortex is also altered after mAMPH (Hotchkiss and Gibb 1980).…”
Section: Discussionmentioning
confidence: 99%
“…A single-day of binge mAMPH has been reported to result in cortical changes, affecting metabolism and gene expression in several cortical areas (Pontieri et al 1990; Belcher et al 2009). Such functional 5-HT changes can occur secondarily to changes in DA transmission (Marshall et al 2007; Belcher et al 2009) and might predispose the organism to work and/or delay aversion. Serotonin in the frontal cortex is also altered after mAMPH (Hotchkiss and Gibb 1980).…”
Section: Discussionmentioning
confidence: 99%
“…However, at the doses used here, single-day binge mAMPH administration produces no loss of serotonin transporter in the cortical areas sampled (Belcher et al, 2008), while even higher binge mAMPH doses—sufficient to produce greater than 50% reductions in striatal dopamine—result in no significant depletion of frontal cortex dopamine (Ohmori et al, 1993). Several groups have reported that a single-day binge mAMPH administration leads to altered functioning of cerebral cortex, affecting metabolism and immediate early gene expression of several cortical areas (including OFC; Pontieri et al, 1990; Belcher et al, 2009). Elsewhere we have hypothesized that these functional changes in cerebral cortex of binge mAMPH-treated rats occur secondarily to the decreases in striatal dopamine, achieved through alterations in striato-nigro-thalamo-cortical loops (Marshall et al, 2007; Belcher et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported that a single-day binge mAMPH administration leads to altered functioning of cerebral cortex, affecting metabolism and immediate early gene expression of several cortical areas (including OFC; Pontieri et al, 1990; Belcher et al, 2009). Elsewhere we have hypothesized that these functional changes in cerebral cortex of binge mAMPH-treated rats occur secondarily to the decreases in striatal dopamine, achieved through alterations in striato-nigro-thalamo-cortical loops (Marshall et al, 2007; Belcher et al, 2009). The basal ganglia-cortical loop hypothesis also provides a useful framework for interpreting the above-mentioned reports of the correspondence between diminished OFC activity and level of D2 receptors found in the brains of stimulant addicts (Volkow et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cortical immediate‐early gene induction by DA receptor agonists is blunted in rats with METH‐induced neurotoxicity (Belcher et al . ). Furthermore, novelty‐induced c‐ fos mRNA expression in striatopallidal neurons is dependent on corticostriatal transmission (Ferguson and Robinson ), sensitive to decreases in D1‐DA receptor activation (Ferguson et al .…”
Section: Discussionmentioning
confidence: 97%
“…Disruption of striatal D1-DA receptor activation decreases cortical excitability (Steiner and Kitai 2000;Yano et al 2006;Gross and Marshall 2009). Additionally, cortical immediate-early gene induction by DA receptor agonists is blunted in rats with METH-induced neurotoxicity (Belcher et al 2009). Furthermore, noveltyinduced c-fos mRNA expression in striatopallidal neurons is dependent on corticostriatal transmission (Ferguson and Robinson 2004), sensitive to decreases in D1-DA receptor activation (Ferguson et al 2003), and sensitive to blockade of NMDA receptors or ERK1/2 signaling (Ferguson et al 2003;Ferguson and Robinson 2004).…”
Section: Discussionmentioning
confidence: 99%